Calculation of the Fission Barrier for a Nucleus (_147^239)U_92, by Two-center Shell Model with Woods-Saxon Potential - أمير تفيحة (Latakia University Journal -Basic Sciences Series, 2022)
The set of equations describing the motion of nucleons and their approach and distance between the two fragments has been solved. The calculations were carried out for the nucleus , and we got a good value compared to the experimental results of the fission barrier, and the other value was not good because the integration had to be done on the five deformation moderators, the energy value corresponding to each level of protons and neutrons was calculated according to the shell model with Woods-Saxon potential, calculations for the five dimensions of deformation must be performed using this software, and can be used to estimate the value of the fission barrier.